2018
DOI: 10.23876/j.krcp.2018.37.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Effects of education on low-phosphate diet and phosphate binder intake to control serum phosphate among maintenance hemodialysis patients: A randomized controlled trial

Abstract: BackgroundFor phosphate control, patient education is essential due to the limited clearance of phosphate by dialysis. However, well-designed randomized controlled trials about dietary and phosphate binder education have been scarce.MethodsWe enrolled maintenance hemodialysis patients and randomized them into an education group (n = 48) or a control group (n = 22). We assessed the patients’ drug compliance and their knowledge about the phosphate binder using a questionnaire.ResultsThe primary goal was to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…Similar to our findings, previous studies have reported better knowledge does not always translate to a better serum phosphate level [ 11 , 22 , 65 , 66 , 67 ]. With the growing body of evidence that educating hemodialysis patients on phosphorus improved serum phosphate levels [ 68 , 69 , 70 , 71 ], it is incumbent upon the healthcare professional community to acknowledge that education programs are indispensable for the optimal management of hemodialysis patients in routine care [ 72 ]. On the other hand, it would be appropriate to consider the application of more interactive approaches or technologies such as the internet and mobile telephones as education tools to extend support beyond the hospital setting, and enhancing accessibility to information aims to improve patients’ self-care management [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, previous studies have reported better knowledge does not always translate to a better serum phosphate level [ 11 , 22 , 65 , 66 , 67 ]. With the growing body of evidence that educating hemodialysis patients on phosphorus improved serum phosphate levels [ 68 , 69 , 70 , 71 ], it is incumbent upon the healthcare professional community to acknowledge that education programs are indispensable for the optimal management of hemodialysis patients in routine care [ 72 ]. On the other hand, it would be appropriate to consider the application of more interactive approaches or technologies such as the internet and mobile telephones as education tools to extend support beyond the hospital setting, and enhancing accessibility to information aims to improve patients’ self-care management [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The level of knowledge reported by our study was similar to what has been reported previously. 19 The possible reasons for patients' superficial knowledge on phosphate dietary control and phosphate binders include patients' difficulty in understanding the complexity of the role of minerals and electrolytes, and their interactions in the body. Additionally, the availability of media information regarding phosphate binders is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…They found no difference in calcium-phosphate products after the education. 11 This may be attributed to patients' lack of discipline over their diet or fatigue with long-term treatment programs.…”
Section: Discussionmentioning
confidence: 99%